Uji Nilai Tahanan Jenis Polutan Air Laut Dengan Metode Ohmik Dan Geolistrik Tahanan Jenis Skala Laboratorium - Dwi Indriana, Rina; Danusaputro, Hernowo (BERKALA FISIKA, 2006)
Geoelectric method and ohmic method used to investigate sea water intrution (salinity) in aquifer layer.Resistivity data aquisition for 3 layer model and 3 concentration of salinity was in laboratory scale. By comparing resistivity data before and after adding sea water we get resistivity value for each layer. The research result is decreasing of resistivity value for increasing salinity concentration.Â  Â